Global burden and trends of Klebsiella pneumoniae infection, 1990–2021: insights from the global burden of disease study - Ju, Jiangang; Liu, Xiaona; Chen, Qingqing; Wang, Jian; Shen, Linfeng (Frontiers in Public Health, 2025)
BackgroundKlebsiella pneumoniae (KP), a prominent member of the Enterobacteriaceae family, is recognized as an opportunistic pathogen responsible for a variety of diseases. Despite its significant threat to public health, there is a lack of epidemiological information concerning the burden of KP infection in the lower respiratory tract.MethodsAge-standardized rates (ASR) of disability-adjusted life-years (DALYs) and deaths rates (ASDRs) attributed to KP infection were obtained from Global Burden of Disease (GBD) 2021, stratified by sex, age, socio-demographic Index (SDI) quintiles and seven super regions. We also calculated the average annual percentage changes (AAPCs) of ASR-DALYs and ASDRs for KP infection using the Joinpoint regression analysis to evaluate the trend of disease burden.ResultsIn 2021, the global ASR-DALYs and ASDRs attributable to KP infection were 124.4 and 2.68 per 100,000, with AAPCs of −3.23% and −2.42%, respectively. The highest burden of ASR-DALYs was observed in children under 5 years of age, with a rate of 775.75 per 100,000 (95% uncertainty interval [UI]: 601.07 to 973.76), while the highest ASDRs were found in individuals over 70 years of age, with a rate of 18.05 per 100,000 (95% UI: 15.84–19.70). Notably, there were significant increasing trends in DALYs and death rates due to KP infection in Central Europe, Eastern Europe, and Central Asia across all age groups above 15 years, with the most pronounced increase observed in individuals over 70 years of age, characterized by AAPCs of 0.85% (95% confidence interval [CI]: 0.64 to 1.05) and 1.00% (95% CI: 0.85–1.17), respectively.ConclusionOver the past 32 years, the global burden of KP infection in the lower respiratory tract has generally declined, but it has increased among the older population in Central/Eastern Europe and Central Asia. This rise is likely due to inappropriate antibiotic use, widespread antimicrobial resistance, emerging virulent and multidrug-resistant strains, and an aging population, highlighting the need for vigilant monitoring and intervention measures.